Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan melalui Work Engagement sebagai Variabel Intervening pada Bagian Sewing PT Sandang Asia Maju Abadi (Kawasan Industri Wijayakusuma Tugu Semarang) - Arindi Rizqi Astuti; Widiartanto Widiartanto; Sudharto P. Hadi (Jurnal Ilmu Administrasi Bisnis, 2023)
Human resources are the most important element in the company. Therefore, companies must have the right way to improve employee performance. PT Sandang Asia Maju Abadi, which is the object of this research, is a garment company that has been established for more than 30 years. In operational activities, the company has a target to continuously improve employee performance to achieve company goals. However, when measured using the Key Performance Indicator, employee performance scores fluctuate every year and even tend to decrease so that the target of increasing employee performance is not fulfilled. The purpose of this study is to determine the effect of discipline and motivation on the performance of the sewing department employees at PT Sandang Asia Maju Abadi through work engagement. This research uses explanatory research type. The sample used a random sampling technique of 100 respondents and the data collection technique used a questionnaire and interviews. The data analysis method used  regression analysis using IBM SPSS version 26.0 tools. The results showed that there was an influence between work discipline on work engagement, work motivation on work engagement, work discipline on employee performance, work motivation on employee performance, and work motivation and discipline on employee performance. The results of the Sobel test stated that there was an effect of work discipline on employee performance through work engagement and work motivation on employee performance through work engagement. The results of the mediation test stated that work engagement is a partial intervening variable in mediating the effect of work discipline on employee performance as well as being a partial intervening in mediating the effect of work motivation on employee performance. The advice given to PT Sandang Asia Maju Abadi is that the company must be firm if there are employees who violate the rules, the company can increase employee morale through various ways such as giving awards to employees who excel.Sumber daya manusia merupakan elemen terpenting dalam perusahaan. Oleh karena itu, perusahaan harus memiliki cara yang tepat untuk meningkatkan kinerja karyawan. PT Sandang Asia Maju Abadi yang menjadi objek pada penelitian ini merupakan perusahaan garmen yang telah berdiri lebih dari 30 tahun. Dalam kegiatan operasionalnya, perusahaan memiliki target untuk terus meningkatkan kinerja karyawan agar dapat mencapai tujuan perusahaan. Akan tetapi, setelah diukur menggunakan Key Performance Indicator, skor kinerja karyawan setiap tahunnya fluktuatif bahkan cenderung menurun sehingga target meningkatnya kinerja karyawan tidak terpenuhi. Tujuan penelitian ini yakni untuk mengetahui pengaruh disiplin kerja dan motivasi kerja terhadap kinerja karyawan bagian sewing pada PT Sandang Asia Maju Abadi melalui work engagement. Penelitian ini menggunakan tipe penelitian explanatory research. Sampel yang digunakan menggunakan teknik random sampling sebanyak 100 responden dan teknik pengumpulan datanya menggunakan kuesioner serta wawancara. Metode analisis data yang digunakan yakni analisis regresi dengan menggunakan tools IBM SPSS versi 26.0. Hasil penelitian menunjukkan terdapat pengaruh antara disiplin kerja terhadap work engagement, motivasi kerja terhadap work engagement, disiplin kerja terhadap kinerja karyawan, motivasi kerja terhadap kinerja karyawan, dan motivasi serta disiplin kerja terhadap kinerja karyawan. Hasil uji sobel menyatakan terdapat pengaruh disiplin kerja terhadap kinerja karyawan melalui work engagement serta motivasi kerja terhadap kinerja karyawan melalui work engagement. Hasil uji mediasi menyatakan bahwa work engagement merupakan variabel intervening parsial dalam memediasi pengaruh disiplin kerja terhadap kinerja karyawan serta menjadi intervening parsial dalam memediasi pengaruh motivasi kerja terhadap kinerja karyawan. Saran yang diberikan kepada PT Sandang Asia Maju Abadi yakni perusahaan harus tegas apabila terdapat karyawan yang melanggar peraturan dan perusahaan dapat meningkatkan semangat kerja karyawan melalui berbagai cara seperti memberikan penghargaan kepada karyawan yang berprestasi.Kata Kunci: Disiplin kerja, Motivasi Kerja, Work Engagement, Kinerja Karyawan.Abstract : Human resources are the most important element in the company. Therefore, companies must have the right way to improve employee performance. PT Sandang Asia Maju Abadi, which is the object of this research, is a garment company that has been established for more than 30 years. In operational activities, the company has a target to continuously improve employee performance to achieve company goals. However, when measured using the Key Performance Indicator, employee performance scores fluctuate every year and even tend to decrease so that the target of increasing employee performance is not fulfilled. The purpose of this study is to determine the effect of discipline and motivation on the performance of the sewing department employees at PT Sandang Asia Maju Abadi through work engagement. This research uses explanatory research type. The sample used a random sampling technique of 100 respondents and the data collection technique used a questionnaire and interviews. The data analysis method used  regression analysis using IBM SPSS version 26.0 tools. The results showed that there was an influence between work discipline on work engagement, work motivation on work engagement, work discipline on employee performance, work motivation on employee performance, and work motivation and discipline on employee performance. The results of the Sobel test stated that there was an effect of work discipline on employee performance through work engagement and work motivation on employee performance through work engagement. The results of the mediation test stated that work engagement is a partial intervening variable in mediating the effect of work discipline on employee performance as well as being a partial intervening in mediating the effect of work motivation on employee performance. The advice given to PT Sandang Asia Maju Abadi is that the company must be firm if there are employees who violate the rules, the company can increase employee morale through various ways such as giving awards to employees who excel.